Improvement of Professional Preparation of Future Teachers by the Computer-Oriented Departmental Teaching (Journal of Information Technologies in Education (ITE), 2008)
By the basic function of the developed program complex the “Electronic magazine” is increase of efficiency of control of knowledges of students of pedagogical university, that is instrumental in the improvement of professional preparation of future teachers.